The effects of soil compactness on the burrowing performance of sympatric eastern and hairy‐tailed moles. (10th December 2016) - Lin, Y.‐F.; Chappuis, A.; Rice, S.; Dumont, E. R.
Abstract: Burrowing is an energetically costly form of locomotion that has evolved multiple times in mammals. Burrowing performance is associated with varying degrees of morphological specialization and is also affected by the characteristics of the substrate that animals burrow in. Moles (Talpidae) are well known for their specialized forelimbs and extreme dedication to life underground. In this study, we investigated how soil compactness affects burrowing performance in two sympatric mole species, eastern moles ( Scalopus aquaticus ) and hairy‐tailed moles ( Parascalops breweri ). We measured burrowing speed, the amount of soil moved, rate of soil transport, tunnel length, activity level and the tendency to burrow over long distances, and tested how these variables changed in response to loose, intermediate and compact soils. We found that increasing soil compactness impedes tunneling performance as evidenced by reduced burrowing speed, increased soil transport, shorter tunnels, shorter activity time and less time spent burrowing continuously. Eastern moles built longer tunnels than hairy‐tailed moles as soil compactness increased. This difference is linked to burrowing for longer times and distances, not higher burrowing speeds or rates of soil transport. Differences in performance between the two species may be associated with differences in the structure and extent of their burrow systems or the morphology of their forelimbs. They may also reflect preferences for loose (hairy‐tailed moles) or compact soils (eastern moles). Abstract : We investigated how soil compactness affects burrowing performance in two sympatric mole species, eastern moles ( Scalopus aquaticus ) and hairy‐tailed moles ( Parascalops breweri ). We found that increasing soil compactness impedes tunneling performance as evidenced by reduced burrowing speed, increased soil transport, shorter tunnels, shorter activity time and less time spent burrowing continuously. Eastern moles built longer tunnels than hairy‐tailed moles as soil compactness increased. This difference is linked to burrowing for longer times and distances, not higher burrowing speeds or rates of soil transport.